Factors that affect the formation of epistemic emotions: The role of "high confidence errors" - Stergiadou, Paraskevi; Nerantzaki, Katerina; Metallidou, Panagiota (Psychology: the Journal of the Hellenic Psychological Society, 2023)
The present study examined the hypothesis that "high confidence errors" will elicit epistemic emotions. The sample consisted of 302 undergraduate and postgraduate students of Greek Universities. The main task was four decision-making scenarios, which force to high confidence common logical errors due to the use of heuristics. Performance in each scenario was followed by an estimation of their feeling of difficulty and of confidence, an external feedback for the correct answer, estimations for epistemic emotions (surprise, curiosity, confusion) and task specific interest. The results verified the hypothesis that high confidence errors consist a significant eliciting factor of basic epistemic emotions, illustrating thus the role of unexpected feedback as a significant elicitor of epistemic emotions. Moreover, it was verified the contribution of cognitive, metacognitive and motivational factors on the formation of epistemic emotions. The theoretical and practical implications of the findings are discussed.